Model Approach In Enforcement Of Perda No 5 Year 2017 About A No Smoking Area (Case Study Of Enforcement Within The Scope Of Opd East Kalimantan Province) - Ajisaka Bagas Satyanagara; Nabielah Fauzia; Nur Anisya Azlin; Wahyu Setiawan (Jurnal Mantik, 2022)
Cigarettes have addictive properties whose use can cause non-communicable diseases (PTM) to active smokers and passive smokers. This research is entitled "A Model Approach in Enforcement of Regional Regulation No. 5 of 2017 concerning Non-Smoking Areas (Case Study of Enforcement within the Scope of OPD of East Kalimantan Province)". Knowing the model approach used in Enforcement of the Regional Regulation on KTR and the resulting output. This study uses a qualitative research method with a descriptive approach. Sources of data using primary and secondary data sources. Data collection techniques were carried out using interviews and documentation. Data analysis techniques were obtained through data analysis, data presentation and drawing conclusions. The approach used in enforcing the Regional Regulation on KTR is a political approach. The governor in this case as the regional head has the power and influence in the regional government organization. Thus, the success of the Perda KTR will help in the appearance of other dominant group governors such as the Head of the OPD to witness a member under him to participate in the success of his policies. Suggestions for further implementation of this policy are expected not only to rely on a limited political approach model. There are still two approaches, namely procedural and managerial approaches through programs and their derivative policies in support of the KTR regional regulation and a behavioral approach that emphasizes awareness of object policies, namely the ASN of each OPD by way of education through socialization.